Ethnic and Confessional Relations Coverage in the Mass Media of the Republic of Tatarstan - Bakanov, Roman P.; Egorova, Liliia; Tumanov, Dmitrii; Tyabina, Diana; Khasanova, Angelica (Journal of History Culture and Art Research, 2018)
The article reveals the key ideologemes in the sphere of interconfessional relations in the Republic of Tatarstan – one of economically developed regions of Russia. The authors analyzed different articles of newspapers with various typological background – “Respublika Tatarstan” (“The Republic of Tatarstan”, the official gazette of the Republic of Tatarstan), “Vremya i Dengi” (“The Time and Money”, the edition for business circles), “Vechernyaya Kazan” (“Evening Kazan”, mass media edition claiming to be an independent one). Applying the methods of substantive (quantitative and qualitative levels of cognition of reality), comparative, and discourse analysis of the newspapers on religious issues published in the Republic of Tatarstan, it was concluded that the republican press sought to adequately reflect the situation in the Republic of Tatarstan for the research period. In addition, the article discovers that a number of regional social problems of religious nature were to be muted in the local newspapers selected for the research. However, if such problems were still discussed, journalists and newspapers’ editors always focused on the settlement of any conflict situations in interconfessional relations. Moreover, in 2000-2017 the local press openly supported the manifestations of interconfessional tolerance, trying to deal with the activities of representatives of Islam and Orthodoxy in equal measure. The image of the “enemy” by faith in the research chronological period was not formed in the mass media, instead, journalists often spoke about the existence of an interconfessional dialogue. The results of our study supplement the findings of W. Gudykunst (1997), M. Kim (1994), M. Bennet (1998) and M. Maruyama (1970) through studying the practice of the print media functioning in one of the polyethnic Russian regions – the Republic of Tatarstan.